Russia's Energy Interests in Azerbaijan: A Retrospective Analysis and Prospective View - Gubad Ibadoghlu (SSRN, 2024)
This paper is a deep dive into the reasons behind Russian President Putin's state visit to Azerbaijan, with a specific focus on Russia's energy interests in the region. The research includes an analysis of key players such as Gazprom and Lukoil in Azerbaijan, and their future plans for energy cooperation with Russia. The article also evaluates the potential impact of Russia's energy interests in Azerbaijan on Europe's energy security, and the feasibility of Azerbaijan meeting its gas supply commitments to Europe.
Keywords: 330; Russia; Azerbaijan; energy; oil; gaz; Gasprom; Lukoil; SOCAR; ACG; Shahdeniz; SGC; BTC